2011
DOI: 10.1016/j.jcin.2010.09.022
|View full text |Cite
|
Sign up to set email alerts
|

Difference of Culprit Lesion Morphologies Between ST-Segment Elevation Myocardial Infarction and Non–ST-Segment Elevation Acute Coronary Syndrome

Abstract: The present OCT study demonstrated the differences of the culprit lesion morphologies between STEMI and NSTEACS. The morphological feature of plaque rupture and the intracoronary thrombus could relate to the clinical presentation in patients with acute coronary disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
76
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 179 publications
(82 citation statements)
references
References 26 publications
4
76
1
1
Order By: Relevance
“…The incidences of plaque rupture (70% versus 47%), thin-cap fibroatheroma (78% versus 49%), and red thrombus (78% versus 49%) were significantly higher in STEMI, compared to NSTEMI patients, and they had a larger ruptured cavity area than NSTEMI patients. 23) Therefore, as damages by infarct transmurality are not relatively serious in NSTEMI compared to STEMI, postinterventional coronary flow could have less influences on overall survival benefit. And, there is a potential for early hazard due to intervention on unstable plaques with fresh thrombus.…”
Section: Discussionmentioning
confidence: 99%
“…The incidences of plaque rupture (70% versus 47%), thin-cap fibroatheroma (78% versus 49%), and red thrombus (78% versus 49%) were significantly higher in STEMI, compared to NSTEMI patients, and they had a larger ruptured cavity area than NSTEMI patients. 23) Therefore, as damages by infarct transmurality are not relatively serious in NSTEMI compared to STEMI, postinterventional coronary flow could have less influences on overall survival benefit. And, there is a potential for early hazard due to intervention on unstable plaques with fresh thrombus.…”
Section: Discussionmentioning
confidence: 99%
“…22 Moreover, plaque rupture was more frequent in STEMI patients than in NSTE-ACS (70% vs. 47%, P=0.033), and cap disruption tended to be directed against the coronary flow in STEMI patients. 25 Fibrous cap thickness is one of the most critical determinants of plaque rupture susceptibility. 12 The widely accepted cut-off point for rupture-prone plaque, 65 μm, was obtained from a pathological study 34 in which the thinnest fibrous cap thickness was measured in 41 ruptured plaques causing sudden cardiac death (95th percentile value, 65 μm).…”
Section: Advances In Imaging Speedmentioning
confidence: 99%
“…In line with the latter interpretation, total cholesterol and LDL values were significantly lower in patients with UA, as compared with STEMI and NSTEMI. Of note, optical coherence tomography (OCT) studies have shown that STEMI patients have larger cavities than those with NSTEMI [19]. A previously published study from the GRACE has also demonstrated that preventive cardiovascular premedication can influence the type of ACS presentation [20] and therefore might modulate clinical outcome.…”
Section: Discussionmentioning
confidence: 99%